Numerical study of unsteady flow and exciting force for swept turbomachinery blades - Zhang Di (Thermal Science, 2016)
The aerodynamic performance of blade affects the vibration characteristics and stable operation of turbomachinery closely. The aerodynamic performance of turbine stage can be improved by using swept blade. In this paper, the RANS method and the RNG k-ε turbulence mode were adopted to investigate the unsteady flow characteristics and excitation force of swept blade stage. According to the results, for the swept blade, the fluid of boundary layer shifts in radial direction due to the influence of geometric construction. It is observed that there is similar wake development for several kinds of stators, and the wake has a notable effect on the boundary layer of the rotor blades. When compared with straight blade, pressure fluctuation of forward-swept blade is decreased while the pressure fluctuation of backward-swept blade is increased. The axial and tangential fundamental frequency excitation force factors of 15°forward-swept blade are 0.139 and 0.052 respectively, which are the least, and all excitation force factors are in the normal range. The excitation factor of the forward-swept blade is decreased compared with straight blade, and the decreasing percentage is closely related to the swept angle. As for backward-swept blades, the situation is the other way around. Additionally, the change of axial excitation factor is more obvious. So the vibration reduction performance of forward-swept blade is better.